Letter from Carl D. Duncan to Patricia Whiting, April 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan discusses travel plans that would interfere with his ability to take Whiting to see the doctor.